An action research case study to examine coaches’ implementation of sport-based trauma-sensitive practices in a nationally-run community program - Shaikh, Majidullah; Bouchard, Melanie; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2021)
Trauma-sensitive practices involve leveraging protective factors (e.g., supportive relationships, sense of safety, opportunities to build skills) to promote healthy development in children’s activities. These practices allow coaches to be responsive to the unique needs of trauma-exposed children, be better equipped to mitigate trauma-related harm, and promote resilience-building. Little research has looked at how coaches apply trauma-sensitive practices in a community sport setting. An action research case study was conducted to examine coaches’ use of sport-based trauma-sensitive practices in multiple sites of a nationally-run community program. Coaches (N = 14 [7 women, 7 men], Mage = 25.86 ± 6.16 years) from six sites running trauma-sensitive sport programs participated in this study (4/6 sites led by trained trauma-sensitive coaches). Coaches were observed as they facilitated a program session, and pre- and post-session focus group interviews were conducted to explore coaches’ perceptions of their goals, design, and delivery of program sessions, and to provide them feedback to improve their practices. Data were captured through audio-video recordings, detailed field notes, and program quality assessments on the Promising Practices Ratings System. All data were interpreted using a deductive-inductive thematic analysis to understand patterns in coaches’ practices. The results showed: (a) evidence of supportive relationships with adults and peers across all observed sessions, (b) coaches experienced challenges in managing children’s dysregulated behaviours and sought to learn more strategies for intervening with these children, and (c) programs led by trained coaches were stronger than untrained coaches in maintaining appropriate structure, maximizing engagement, and providing opportunities for cognitive growth (i.e., discussing life skills). Implications are discussed related to the successes and challenges of delivering trauma-sensitive practices in this community sport setting, the value of training in coaches’ facilitation of high-quality sport programs.
Keywords: community-engaged; trauma-informed; assessment and feedback